(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2025)
The exponential growth of the Internet of Things (IoT) has revolutionized communication networks, enabling intelligent applications across various domains. However, the decentralized and resource-constrained nature of IoT networks introduces significant security and privacy concerns, especially in routing mechanisms. This paper provides a comprehensive analysis of secure routing protocols designed for IoT networks. It explores the threats and challenges unique to IoT routing, evaluates existing secure routing protocols, and discusses emerging trends and future directions for achieving robust and scalable security in IoT communication systems.)